Exposure to competitors influences parasitism decisions in ectoparasitoid fly larvae. (February 2015) - Crespo, J.E.; Martínez, G.A.; Castelo, M.K.
Abstract : Much theoretical work has been done regarding patch exploitation in insects and several mechanisms have been proposed to describe and predict behaviours under different situations. However, almost no theoretical framework has been developed for parasitoids with host-seeking larvae, even though similar selection pressures are faced by the female of hymenopteran parasitoids and the larvae of dipteran parasitoids. Here we propose and show that factors such as pre-parasitism competition and host physiological state can modulate host orientation and acceptance behaviours in a dipteran parasitoid larva. When larvae were exposed to pre-parasitism competition and then offered different host odours and live hosts, they oriented towards and more readily accepted suboptimal hosts and were more prone to superparasitize. Our results show that the internal state modulates individual decisions that dipteran parasitoids make, confirming the presence of many previously neglected strategies in parasitoids with host-seeking larvae. Hence, comparative studies should be undertaken to form a complete picture of parasitism strategies. Highlights: We studied the influence of pre-exposure to conspecifics on host orientation decisions of parasitoid flies. Pre-exposed larvae lowered their selectivity threshold of suboptimal hosts. Individually raised larvae remained highly selective of optimal hosts.